2005
DOI: 10.1016/j.joca.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of subchondral bone resorption pits in osteoarthritis: MMP production by cells derived from bone marrow

Abstract: These results suggest that subchondral bone resorption pits contribute to cartilage degradation by expressing matrix metalloproteinases in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 23 publications
7
70
0
1
Order By: Relevance
“…A case-control study similarly found reduced peak bone mass at the femoral neck in very LBW babies (3). There is emerging evidence that preterm birth and very LBW result in a decrease in bone formation and increase in bone resorption (23,24) that reduced osteoclast apoptosis (25) and cartilage degeneration (26), which may be another potential pathway of development of hip OA.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study similarly found reduced peak bone mass at the femoral neck in very LBW babies (3). There is emerging evidence that preterm birth and very LBW result in a decrease in bone formation and increase in bone resorption (23,24) that reduced osteoclast apoptosis (25) and cartilage degeneration (26), which may be another potential pathway of development of hip OA.…”
Section: Discussionmentioning
confidence: 99%
“…We are faced with a complex interaction between local events in the joint, pain sensitization, the cortical experience of pain, and what people are doing in their everyday lives. There is a vast body of evidence to suggest that OA is a heterogenous condition that involved not only the articular cartilage but also an adaptive response of the bone and the synovium to a variety of environmental, genetic and biomechanical stresses (Denko et al 1996, Pelletier et al 1996, Westacott et al 1996, Fink et al 2001, Volck et al 2001, Yuan et al 2004, Shibakawa et al 2005. There is also growing evidence pointing towards LTP as the most likely mechanism for the transition of acute nociception to a CP state.…”
Section: Resultsmentioning
confidence: 99%
“…Beside the inflammation of the synovium, the synovium has equally be linked with the production of high levels of interleukin-1 (IL-I), tumour necrosis factor-α (TNF-α), and cytokines. Cytokines and the other substances released from the cartilage, synovium and the bone invariably affect the chondrocyte function and when catabolism exceeds cartilage synthesis, osteoarthritis develops (Denko et al 1996, Pelletier et al 1996, Westacott & Sharif 1996, Fink et al 2001, Volck et al 2001, Yuan et al, 2004, Shibakawa et al 2005.These complex series of events result in the early changes seen in OA as outlined below:…”
Section: Pathophysiology Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Following staining with Mayer's haematoxylin solution and 1% eosin alcohol solution (H&E staining), the total number of cystic lesions that invaded the subchondral bone plate or calcified zone were counted from three slides that corresponded to weight-bearing areas. Density of cystic lesions was expressed as the number of cystic lesions per 10-mmlength of specimen [11]. Correlation of parameters related to irregularity of the contour on MRI and the density of cystic lesions were examined.…”
Section: Specimens and Histological Evaluationmentioning
confidence: 99%